Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for peritoneal malignant tumors in children: Initial experience in a single institution - Zhu, Zhiyun; Chang, Xiaofeng; Wang, Jiarong; Yang, Shen; Qin, Hong; Yang, Wei; Cheng, Haiyan; Meng, Deguang; Wang, Huanmin (Frontiers in Surgery, 2023)
Background Peritoneal malignant tumors in children are rare but commonly associated with disease progression and poor outcome. The successful treatment experience of cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) in adult peritoneal carcinoma has been applied to pediatric peritoneal malignancy in recent years. However, patients with desmoplastic small round cell tumor (DSRCT) accounted for the majority of patients treated with CRS and HIPEC in previous studies. The role of CRS and HIPEC remains controversial due to the rarity of the disease and the limited sample size of studies. Additionally, the cases using CRS and HIPEC except DSRCT were mainly small case reports with unclear outcomes. We present our experience in the treatment of pediatric peritoneal malignancies using CRS and HIPEC, with more emphasis on the safety, feasibility, and short-term outcome. Methods A retrospective query from December 2019 to February 2022 identified 19 children with peritoneal malignancies who underwent CRS and HIPEC in our institution. Clinical characteristics, therapies, and outcomes were summarized and analyzed. Results The median age of the patients was 6.4 years (range, 0.7–13.9 years). The histologic types included rhabdomyosarcoma (7), Wilms tumor (2), clear cell sarcoma of the kidney (2), undifferentiated sarcoma (2), immature teratoma (1), peritoneal serous carcinoma (1), malignant rhabdoid of the kidney (1), malignant germ cell tumor (1), neuroblastoma (1), and epithelioid inflammatory myofibroblast sarcoma (1). Seven patients underwent initial operation, and 12 patients received reoperation for tumor recurrence. The median peritoneal carcinomatosis index was 5 (range, 2–21). There were no perioperative deaths or life-threatening complications of CRS and HIPEC. Two patients had grade 3 complications of wound infection and wound dehiscence. With a median follow-up time of 14 months (range, 1.5–31 months), 14 patients were alive, and 5 died of tumor recurrence. Of the 14 patients who were alive, 2 relapsed after CRS and HIPEC and then received radiotherapy and molecular-targeted therapy or chemotherapy. Conclusions CRS and HIPEC are safe and feasible in children, without increasing serious complications in the peri- and postoperative periods. The complication is acceptable. The short-term outcome shows possible effectiveness in pediatric peritoneal malignant tumors. The long-term effectiveness needs to be verified by additional cases and long-term follow-ups.